Transitory Cognitive Deficit with Epilepsy Paroxysm - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2000)
The EEGs and cognitive responses during a go-no go Continuous Performance Test (CPT) were studied in two groups of 58 epileptic and 20 healthy control chiuldren, ages 8 to 12 years, at the Hospital Civil de Guadalajara, Mexico.